2004
DOI: 10.1046/j.1365-2648.2003.02927.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the postnatal outcomes of new mothers

Abstract: Findings indicate that the extra training of MCHN did not substantially assist in the detection and management of postnatal distress in these new mothers. Unexpected ecological conditions of workforce disruption and extra workloads may have mitigated against the success of the programme. Limitations of the study are examined and the implications for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…The prevalence rates in this study dropped from 13.2% at 6 weeks to 9.8% at 12 weeks, similar to findings from previous research with rates of 10.6% (Morse, Durkin, Buist, andMilgrom, 2004) and10.2% (Righetti-Veltema, Conne-Pereard, Bousquet, &Manzano, 1998) at 12 weeks. Matthey, Barnett, Judy, and Waters (2000) reported an even lower prevalence rate of 6.4% at 4 months.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence rates in this study dropped from 13.2% at 6 weeks to 9.8% at 12 weeks, similar to findings from previous research with rates of 10.6% (Morse, Durkin, Buist, andMilgrom, 2004) and10.2% (Righetti-Veltema, Conne-Pereard, Bousquet, &Manzano, 1998) at 12 weeks. Matthey, Barnett, Judy, and Waters (2000) reported an even lower prevalence rate of 6.4% at 4 months.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, one Australian study of 327 first-time couples where 12% of the men were distressed at mid-pregnancy, found that men 0 s distressed mood (EPDS4 10) was related to low emotional support from the female partner, low dyadic adjustment, anxiety and high gender role stress, and fears of performance failure. Predictors of male postnatal distress were perceived sense of being controlled, the relationship being less than two years and being younger than 31 years of age (Morse et al, 2004). Finally our work identified that expectant fathers with fear of childbirth had higher levels of parental stress one year after birth.…”
Section: Discussionmentioning
confidence: 57%
“…Several studies suggest that the EPDS is a good measure of distress levels among mothers (Fisher et al 2002;Morse et al 2004). In fact, this instrument reflects the symptoms included in the concept of maternal distress as an emotional response experienced by mothers (Emmanuel et al 2011).…”
Section: Clinical Assessmentmentioning
confidence: 99%